THEORETICAL ASPECTS OF THE INFLUENCE OF SOCIO-ECOLOGICAL FACTORS ON EFFECTIVE USE OF LABOR RESOURCES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article examines the theoretical aspects of the impact of social and environmental factors on the efficient use of labor resources. In particular, the deterioration of the socio-ecological situation leads to the emergence of temporary disability for workers at industrial enterprises.